2014
DOI: 10.1039/c3np70081j
|View full text |Cite
|
Sign up to set email alerts
|

A natural prodrug activation mechanism in the biosynthesis of nonribosomal peptides

Abstract: Highlight describes the recently discovered prodrug activation mechanism found in the biosynthesis of nonribosomally produced peptides and peptide/polyketide hybrids as well as related mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
47
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 41 publications
4
47
0
1
Order By: Relevance
“…[8] Therefore,i nhibition of ClbP by small molecules could confer protection against colibactininduced colorectal cancers. [9] Thei dentification of similar prodrug activation mechanisms in other natural products derived from NRPS and PKS/ NRPS hybrids revealed aw idespread occurrence of such am echanism, [10] which was originally identified for the antibiotic xenocoumacin from Xenorhabdus nematophila. [11] There,i tw as shown that acylated prexenocoumacins are cleaved after ac onserved d-asparagine upon secretion from the cell, which results in the active antibiotic xenocoumacin 1.…”
Section: Angewandte Highlightsmentioning
confidence: 99%
“…[8] Therefore,i nhibition of ClbP by small molecules could confer protection against colibactininduced colorectal cancers. [9] Thei dentification of similar prodrug activation mechanisms in other natural products derived from NRPS and PKS/ NRPS hybrids revealed aw idespread occurrence of such am echanism, [10] which was originally identified for the antibiotic xenocoumacin from Xenorhabdus nematophila. [11] There,i tw as shown that acylated prexenocoumacins are cleaved after ac onserved d-asparagine upon secretion from the cell, which results in the active antibiotic xenocoumacin 1.…”
Section: Angewandte Highlightsmentioning
confidence: 99%
“…Similar NRPS have been shown to be involved in the biosynthesis of piperazines or terphenylquinones from fungi (48,49). The largest gene cluster (cluster 4) encodes an NRPS-PKS hybrid with all structural features of the prodrug activation mechanism previously identified in the biosynthesis of xenocoumacin, zwittermicin, and colibactin (39,(50)(51)(52). Additionally, a putatively incomplete NRPS-PKS hybrid gene cluster (cluster 5 in Fig.…”
Section: Artificial Rearingmentioning
confidence: 99%
“…[3] This reaction requires ac ryptic fatty acyl chain for substrate recognition ( Figure 1). [4] Analogously,i ti se xpected that am aturating step is required in the biosynthesis of SFM-A from Streptomyces lavendulae;h owever the corresponding enzymatic reaction is obscure.T he cleavage of the fatty acyl chain releases af ree amino group at C25, and further deamination is needed to afford the C25 keto group in SFM-S (2; Figure 1). [4] Analogously,i ti se xpected that am aturating step is required in the biosynthesis of SFM-A from Streptomyces lavendulae;h owever the corresponding enzymatic reaction is obscure.T he cleavage of the fatty acyl chain releases af ree amino group at C25, and further deamination is needed to afford the C25 keto group in SFM-S (2; Figure 1).…”
mentioning
confidence: 99%
“…Given that all known prodrug-maturation processes occur outside the cell membrane, [4,6] then ext deamination step is most probably performed extracellularly by as ecreted enzyme containing an N-terminal signal peptide.G uided by this information, we searched for as ecreted enzyme,w hose function remained unverified, among the proteins encoded by the sfm gene cluster.SfmCy2 was found to harbor a27amino acid, N-terminal signal-peptide sequence corresponding to af amily of twin-arginine translocation (Tat) signal peptides with conserved aR R-AXA sequence (see Figure S3). [9] Importantly,t he Tats ystem has been proven to be am ajor general route for protein export in Streptomyces.…”
mentioning
confidence: 99%
See 1 more Smart Citation